Complex Interrelations of Trait Vulnerabilities in Mothers and their Infants. (17th January 2015) - Gratz, Kim L.; Kiel, Elizabeth J.; Latzman, Robert D.; Moore, Sarah A.; Elkin, T. David; Megason, Gail C.; Tull, Matthew T.
<x xml:space="preserve">Abstract</x> Despite the developmental and clinical relevance of this area of inquiry, no studies have examined the interrelations of trait vulnerabilities in the affective, behavioral, and interpersonal domains between mothers and their infants. Thus, this study examined the interrelations of three trait vulnerabilities (i.e., negative affective intensity, impulsivity, and insecure attachment) between mothers and their 12‐ to 23‐month‐old infants, focusing in particular on the unique and interactive influence of these maternal trait vulnerabilities on the expression of and precursors to these traits in their infants. Mother–infant dyads (N = 101) completed several laboratory procedures, and mothers reported on their own and their infants' expressions of the trait vulnerabilities of interest. Findings from this study provide preliminary evidence for intergenerational relations between these traits and suggest that it is the confluence of trait vulnerabilities in mothers that relates to the early expression of some of these traits in infants.